Service quality and customer satisfaction in the environment of higher education: a study on the public and private university students in Malaysia / Zainudin Awang, Rustam Shaari and Meer Zhar Farouk Amir Razli - Awang, Zainudin; Shaari, Rustam; Amir Razli, Meer Zhar Farouk (2005)
Quality has become a reality; and the quality related activity is top priority in a university. Lately, the university emphasizes a policy to assure quality such as "Total Quality Management': "Continuous Quality Improvement", "ISO 9000" and "Quality Assurances' One would argue how the service industry such as university assures its service quality. This study provides a framework for service quality measurement in higher education, particularly the university. The purpose of this study is to examine the service quality items and determine the relevant dimensions that constitutes quality in higher education and applicable to the Malaysian situations. The researcher examines various service quality models developed for measuring service quality on various service industry. This study also reviews certain service quality dimensions developed for higher education across the geographical area. Based on various service literatures, the researcher employs a disconfirmation gap (perception - expectation) to measure students' disconfirmation regarding service quality at their university. This study also focuses on tracking to understand students' perception and expectation by examining how these two constructs moderated by certain demographic variables. A structured interview and questionnaire conducted among 616 students from the selected public and private universities. This study discovered five factors that constitute service quality in higher education. The study revealed significant gaps exist in students' disconfirmation of service quality across all dimensions within both types of university. However, the disconfirmation gap of service quality performance between two types of university is not significant; hence, the type of university is not a factor. The hypotheses results show that age and parents' income of students have moderating effect on their satisfaction regarding service quality delivered by the university. Meanwhile, this study also proved that the length of association with the university has a significant influence on students' perception, expectation, and hence satisfaction. The university should measure its service quality performance from the students' perspective and make concerted efforts to adjust to their quality policy accordingly so that the best disconfirmation gap will become a reality in the higher education industry.